2017
DOI: 10.4103/0976-0105.195130
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic Drugs-induced Stevens-Johnson syndrome: A case Series

Abstract: Stevens–Johnson syndrome (SJS) is an acute life-threatening mucocutaneous reaction, characterized by extensive necrosis and detachment of the epidermis from the skin. The overall incidence of SJS is seen in five cases per million people per year. SJS is typically caused by drugs and is a kind of idiosyncratic reaction. Adverse drug reactions such an SJS have a remarkable effect on patient's safety issues. We encountered nine cases of antiepileptic drug (AED)-induced SJS, specifically with carbamazepine, oxcarb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…There are only a few case presentations of OXC-induced SJS in the literature [3, 9]. To the best of our knowledge, our patient is the youngest of all among the cases reported so far in the literature.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…There are only a few case presentations of OXC-induced SJS in the literature [3, 9]. To the best of our knowledge, our patient is the youngest of all among the cases reported so far in the literature.…”
Section: Discussionmentioning
confidence: 78%
“…Although carbamazapine is the major anti-epileptic drug associated with SJS/TEN; OXC-induced SJS/TEN is extremely rare with the incidence of 0.5–6/1.000.000 in 1 year in normal population according to the FDA. There are only a few case presentations of OXC-induced SJS in the literature [ 3 , 9 ]. To the best of our knowledge, our patient is the youngest of all among the cases reported so far in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Greater than 90 percent of SJS/TEN reactions associated with AEDs occur within the first 2 months of treatment initiation, 41 although some AEDs have been associated with such reactions during long term use (phenobarbital and valproic acid). 1 Previous studies have indicated that SJS/TEN reactions may be associated with the starting dose and rate of titration for some AEDs.…”
Section: Discussionmentioning
confidence: 99%
“…If the relationship between LTG accumulation in melanin-rich tissues and SJS is confirmed, it could lead to the development of better strategies to reduce the risk of SJS in individuals taking LTG. This could improve patient outcomes and increase the overall safety and efficacy of LTG as a treatment option [ 127 ].…”
Section: Side Effects Of Lamotriginementioning
confidence: 99%